Balance and deep connections: the impact of physical activity on body and sexual self-esteem, psychological distress, and marital satisfaction among adults - Snani, Haifa; Snani, Hela; Tannoubi, Amayra; Chortane, Oussama Gaied; Azaiez, Fairouz (Frontiers in Sports and Active Living, 2024)
To date, no research has examined the relationship between sexual self-esteem, body selfesteem, psychological distress, marital satisfaction, and engagement in physical activities. Through a study involving 443 adults the aim of this research was to analyze the connections between engaging in physical activities, body self-esteem, sexual self-esteem, marital satisfaction, and psychological distress among adults. The results obtained through Partial Least Squares (PLS) modeling with SmartPLS reveal significant interconnections among these variables. The correlation between body self-esteem and psychological distress, the positive relationship between sexual satisfaction and positive sexual self-esteem, as well as the beneficial influence of engaging in physical activities on marital satisfaction, are key highlights of this study. The robustness of the measures, confirmed by high coefficients, strengthens the credibility of the results. Despite these advancements, the cross-sectional nature of the study emphasizes the need for longitudinal research to gain a deeper understanding of psychological and relational dynamics over time. In conclusion, this study offers significant contributions to promoting balanced marital relationships, highlighting the importance of considering body and sexual self-esteem, psychological distress, and physical activity within the context of human relationships.